PENGARUH STRINGENCY, KORUPSI, DAN PAJAK LINGKUNGAN TERHADAP FOREIGN DIRECT INVESTMENT INFLOW: SEBUAH POLLUTION HEAVEN HYPOTHESIS - Windy Hikmah Ariyani; Unggul Heriqbaldi (EKUITAS (Jurnal Ekonomi dan Keuangan), 2023)
This study aims to analyze the pollution heaven phenomenon, in the case of Foreign Direct Investment (FDI) inflow from the perspective of environmental regulations (stringency), corruption, environmental taxes, and the interaction variables between stringency and corruption. Additionally, this study will investigate the impact of pollution heaven on GDP per capita, labor, and trade openness to FDI inflow. This study used the System Generalized Method of Moments estimations for 6 investor countries of the palm oil sector in Indonesia from 2009 to 2019. The main results show that stringency and corruption have a significant positive effect while the interaction between stringency and corruption has a significant negative effect on FDI inflow in the Indonesian palm oil sector. Loose environmental regulations combined with a honest bureaucracy will prevent investors from receiving legal protection. This condition indicates a significant relationship of the interaction variable between stringency and corruption on FDI inflow, therefore the pollution heaven hypothesis is invalid. Government policy regarding stringency can be improved by implementing environmental taxes. Policies related to corruption are necessary to simplify bureaucratic procedures for investors. The combination of these regulations is expected to help the Indonesian government attract FDI inflows without turning Indonesia into a pollution heaven.